Efforts needed for preventing breast and colorectal cancer through changes in dietary patterns. (7th January 2021) - Mullie, Patrick; Guillot, Gilles; Pizot, Cécile; Autier, Philippe; Boyle, Peter
Abstract: Background: Prospective cohort studies on diet and cancer report risk associations as hazard ratios. But hazard ratios do not inform on the number of people who need to alter their dietary behaviours for preventing cancer. The objective of this study is to estimate the number of people that need to alter their diet for preventing one additional case of female breast or colorectal cancer. Methods: Based on the largest prospective studies done in the USA and in Europe, we computed the number of subjects who need to alter their diet. Results: For preventing one case of breast cancer, European women should increase their fruit consumption by 100 g/day during 33 000 person-years, and US women by 60 g/day during 10 600 person-years. For vegetables, European women should increase their consumption by 160 g/day during 26 900 person-years and US women by 100 g/day during 19 000 person-years. For preventing one case of colorectal cancer, European subjects should decrease their red meat consumption by 20 g/day during 26 100 person-years, and US subjects by 30 g/day during 8170 person-years. For processed meat, European subjects should decrease their consumption by 20 g/day during 17 400 person-years, and US subjects by 10 g/day during 7940 person-years. Conclusions: Large number of subjects would need to alter their intake of fruits, vegetables, red and processed meat during many years in order to prevent one additional breast or colorectal cancer.